Geochemical characteristics of the Permian marine mudstone and constraints on its provenance and paleoenvironment in the Fenghai area, Fujian Province, southeastern China - Qi-Feng Xie (KeAi Communications Co., Ltd., 2019)
Abstract Permian marine strata have gradually become a research focus in the world. The marine strata of the Late Permian Dalong Formation (P3 d) in the Fenghai area, Fujian Province, have become more and more important as their geochemical characteristics record important geological information and are a good indicator for recovering and reconstructing the paleo-sedimentary environments and tectonic attributes. The major elements, trace elements and rare earth elements were analyzed by XRF and ICP-MS, respectively. Based on the results of detailed field geological surveys, profile measurements as well as typical sample collection, the tectonic setting and provenance of Permian marine mudstone were comprehensively discussed. The results showed that the Dalong Formation (P3 d) was deposited in an active continental margin tectonic environment as revealed by the relation between Fe2O3 + MgO and TiO2 and Al2O3/SiO2. The fingerprint characteristics of Mn, Fe, Co, Ni and REE and the ratio of U/Th, V/Cr, Sr/Ba, (La/Yb) N and V/(V + Ni) indicated that the sedimentary provenance was mainly derived from potassium feldspar, followed by muscovite. Sedimentary water bodies showed a gradually decreasing depositional rate trend, water depth gradually shallowing and paleo-salinity and productivity gradually increasing. Moreover, since transient delamination occurred during sedimentary processes, sedimentary water bodies showed obvious neritic characteristics. It was consistent with the results revealed by lithological and geochemical characteristics. Calcareous mudstone and siltstone transitioned into fine sandstone from bottom to top, indicating paleo-water bodies became shallow. The research results provided good reference and guidance for understanding Permian paleo-sedimentary environments and tectonic attributes of the Yong’an area, Fujian Province, southeastern China.